Pengaruh Pemberian Variasi pH terhadap Produksi Trigliserida Total dan Komposisi Asam Lemak dari Chlorella Vulgaris Air Tawar - Wulandari, Rahmadani; Dharma, Abdi; Syafrizayanti, Syafrizayanti (Jurnal Riset Kimia, 2019)
Chlorella vulgaris is a microalgae that has high lipid content and potential as raw material for biofuel production. This study aims are to determine the effect of pH on growth, lipid production and fatty acid composition of C. vulgaris by using Growmore 32-10-10 fertilizer as a culture medium. Microalgae were cultured in medium Growmore 32-10-10 for 10 days. Afterward, pH of medium was varied into pH 5, 7, 8.2 and 9 and continued cultivate for 3 days. C. vulgaris cultured at pH 8.2 which is a control pH reached optimum growths. The GC-MS analysis for lipid productivity of C. vulgaris was 0.5020 g/L/day and 0.2902 g/L/day for microalgae grew at pH 8.2 and 9, respectively. Cultures at pH 8.2 and 9 produce methyl hexadecanoate, methyl 9-octadecanoate, methyl octadecanoate, methyl 9,12-octadecadienoate, methyl 9,11-octadecadienoate. Additional fatty acid methyl nonadecanoate was also found in C. vulgaris grew at pH 9. The low and high pH stress of C. vulgaris culture medium did not affect culture growth but altered lipid production and fatty acid composition.